Human Capital Management: comparison in the location of softwares of human capital management among the countries Brazil, Argentina and Mexico - Dalfovo, Oscar; Dias, Dilson (Review of Business Management, 2009)
The area of staff administration has initiated inside of the organizations a process that today is the great focus of investments in the search of market competitiveness so tough in times of strong globalization, the human capital management. For some time, the organizations have already realized that the differential to be competitive is not in what is produced but in the people who make this process a reality. As the age of the knowledge is currently lived, software of human capital management came to improve the management of these human resources, enabling a more agile dissemination process. As much as the fast expansion of software, the companies have extended to several regions of the planet, which generates the demand of having appropriate software to the local conventions, whether localized it or not. Software localization is an area of recent studies, but has investments research centers by multinational. As general objective of this research, it was sought the comparison of the main pertinent information from the area of personnel management between Brazil, Argentina and Mexico, for the localization of human capital management, so to form and to inspire other researchers to explore this subject in other areas of Administration. The research used the comparative method. As for the objectives it can be classified as descriptive and exploratory; as for the procedures it can be classified as bibliographic and documentary; and as for the approaching of the problem, it can be classified as quantitative and qualitative. Structured questionnaires were applied in companies of Argentina and Mexico, and the analysis of the results showed that it was possible to identify which are the areas of performance of higher adhesion in these countries, and mainly which is the information of greater and minor adhesion for the localization of Brazilian software. The use percentage of current software of human resources, as well as the presentation of the most indicated in the research software, complements the analysis of the results. Finally, it was concluded that is possible to bring to reality the integrated management of all organizational information among others countries, mainly with Argentina, Mexico and Brazil. Key words: Personnel management. Human capital management. Software localization. Knowledge management.